Parâmetros oftálmicos em cães adultos da raça Shih Tzu - Kobashigawa, Karina Kamachi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Ocular surface diseases are often diagnosed in brachycephalic dogs, since their eyes are more exposed. Among the most commonly affected breeds, Shih Tzu dogs are part listed and this breed’s ophthalmic standards are not totally known. In this study ophthalmic standards of this breed were partly studied under physical restraint. Schirmer tear test, break up time test, aesthesiometry, biomicroscopy, non contact specular microscopy, laser flaremetry, applanation tonometry, ultrasonography and ophthalmoscopy were carried in 48 eyes of 24 male and female dogs, with ages from two to four years, weighing between five and 10 kg. All dogs were from a breeding kennel. Descriptive statistics was applied to the data. Mean and standard error for Schirmer tear test was 26.145±0.803 mm/min, for break up time test was 13.668±0.538 s, for aesthesiometry was 2.395±0.071 cm. When evaluated with biomicroscopy 70.83% of the eyes showed medial entropion, 42% showed caruncle trichiasis, 33% distichiasis, 27% corneal opacity and 13% corneal melanosis. Mean and standard error for endothelial cell density was 2221.591±20.161cells/mm2, for endothelial cell hexagonality was 63.770±1.805 %; for endothelial cell area was 451.895±4.179 mm2; for central corneal thickness was 0.490±0.007 mm, for laser flaremetry was 1.720±0.216 PC/ms, for applanation tonometry was 16.118±0.460 mmHg, for axial lenght was 20.255±0.134 mm, for lens thickness was 6.624±0.031 mm, for anterior chamber was 4.064±0.109 mm and for vitreous chamber was 9.565±0.054 mm. Ophthalmoscopy findings were not different from previous reports in other breeds. According to the results obtained, ophthalmic Shih Tzu standards did not differ from reports in other breeds, except for break up time and Cochet-Bonnet aesthesiometry

Afecções da superfície ocular são frequentes em cães braquicefálicos, pela maior exposição do bulbo do olho e por suas intercorrências. Dentre as raças comumente acometidas, tem-se a Shih Tzu, cujos parâmetros oftálmicos não são conhecidos em sua plenitude e foram, em parte, avaliados nesta pesquisa. Sob contenção física, empregou-se o teste lacrimal de Schirmer, o de ruptura do filme lacrimal, a estesiometria, a biomicroscopia com lâmpada em fenda, a microscopia especular de não contato, a flaremetria a “laser”, a tonometria de aplanação, a ecografia e a oftalmoscopia. Foram estudados 48 olhos em 24 indivíduos machos ou fêmeas, com idades variando entre dois a quatro anos e peso entre cinco a 10 Kg, provenientes de canil de criação. Aos dados aplicou-se a estatística descritiva. Relativamente às médias e aos erros padrão, encontraram-se, quanto ao teste lacrimal de Schirmer, 26,145±0,803 mm/min e à ruptura do filme lacrimal, 13,668±0,538 s. À estesiometria, encontraram-se 2,395±0,071 cm. À biomicroscopia, observaram-se 70,83% dos olhos com entrópio de canto medial, 42% apresentaram pelos em carúncula medial, 33% distiquíase, 27% mácula e 13% melanose corneal. Médias e erros padrão, no que concerne à densidade de células endoteliais, foram de 2221,591±20,161 céls/mm2. Quanto à hexagonalidade, foram de 63,770±1,805 %; quanto à área, foram de 451,895±4,179 mm2; e em relação à espessura corneal, de 0,490±0,007 mm. À flaremetria a “laser”, encontraram-se 1,720±0,216 PC/ms e à tonometria, 16,118±0,460 mmHg. As médias e os erros padrão, à ultrassonografia, foram de 20,255±0,134 mm para diâmetro axial horizontal, de 6,624±0,031 mm para espessura da lente, de 4,064±0,109 mm para profundidade da câmara anterior e de 9,565±0,054 mm para a da vítrea O padrão observado à oftalmoscopia não divergiu do já reportado em indivíduos de ...
Keywords: Cão; Oftalmologia veterinaria; Olhos - Exame; Valores de referencia (Medicina); Cão - Raças; Veterinary ophthalmology